Solution‐Processed Polymer Solar Cells with over 17% Efficiency Enabled by an Iridium Complexation Approach. Issue 22 (21st April 2020) - Wang, Tao; Sun, Rui; Shi, Mumin; Pan, Fei; Hu, Zhicheng; Huang, Fei; Li, Yongfang; Min, Jie
Abstract: The commercially available PM6 as donor materials are used widely in highly efficient nonfullerene polymer solar cells (PSCs). In this work, different concentrations of iridium (Ir) complexes (0, 0.5, 1, 2.5, and 5 mol%) are incorporated carefully into the polymer conjugated backbone of PM6 (PM6‐Ir0), and a set of π‐conjugated polymer donors (named PM6‐Ir0.5, PM6‐Ir1, PM6‐Ir2.5, and PM6‐Ir5) are synthesized and characterized. It is demonstrated that the approach can rationally modify the molecular aggregations of polymer donors, effectively controlling the corresponding blend morphology and physical mechanisms, and finally improve the photovoltaic performance of the PM6‐Ir x ‐based PSCs. Among them, the best device based on PM6‐Ir1:Y6 (1:1.2, w/w) exhibits outstanding power conversion efficiencies (PCEs) of 17.24% tested at Wuhan University and 17.32% tested at Institute of Chemistry, Chinese Academy of Sciences as well as a certified PCE of 16.70%, which are much higher than that of the control device based on the PM6‐Ir0:Y6 blend (15.39%). This work affords an effective approach for further break through the reported champion PCE of the binary PSCs. Abstract : Different concentrations of iridium complexes are introduced into the conjugated backbone of polymer donor PM6 (PM6‐Ir0), this strategy can rationally modify the molecular aggregations, effectively control the blend morphology and physical mechanisms, and finally improve the photovoltaic performance. This work affords an effective approach for further breakthroughs in the reported champion power conversion efficiency of polymer solar cells.